1967
DOI: 10.2135/cropsci1967.0011183x000700060024x
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Increased Lint Yield and Correlated Responses in Upland Cotton, Gossypium hirsutum L.1

Abstract: Three cycles of recurrent selection for increased lint yield in Upland cotton (Gossypium hirsutum L) have been completed. Yield of the third cycle selections exceeded that of the base population by 29.7%. Response to selection was linear and is predicted to continue at approximately the same rate of gain for an additional cycle.Correlated responses to selection for yield were observed for the majority of the unselected traits measured. As selection increased lint yield, simultaneous increases were observed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
90
2
8

Year Published

1982
1982
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 0 publications
9
90
2
8
Order By: Relevance
“…To make cotton cultivation sustainable and competitive on the world market, it is imperative to develop early maturing, productive cotton cultivars producing finer (moderately lower micronaire (MIC)) and longer fibres with improved strength 6 . Conventional breeders have faced serious challenges because of negative correlations between fibre quality traits and yield components 6,7 , and between fibre quality and maturity 8 . We hypothesized that phytochrome genes could play a significant role in the regulation of cotton fibre length 9 .…”
mentioning
confidence: 99%
“…To make cotton cultivation sustainable and competitive on the world market, it is imperative to develop early maturing, productive cotton cultivars producing finer (moderately lower micronaire (MIC)) and longer fibres with improved strength 6 . Conventional breeders have faced serious challenges because of negative correlations between fibre quality traits and yield components 6,7 , and between fibre quality and maturity 8 . We hypothesized that phytochrome genes could play a significant role in the regulation of cotton fibre length 9 .…”
mentioning
confidence: 99%
“…The fiber length is critical for the textile industry and varies greatly among the types of cotton due to their genetic differences (Basra, 2000). In some previous studies, authors have reported little or no genetic gain in fiber length (Miller and Rawlings, 1967;Bridge et al, 1971;Bridge and Meredith, 1983;Culp and Green, 1992). Schwartz and Smith (2008) have reported progress in the improvement of fiber length with the release of new cultivars in the USA.…”
Section: Resultsmentioning
confidence: 99%
“…The recurrent selection procedures are also suggested for often cross pollinated crops by considering cotton as an example (Miller and Rawlings, 1967) and in sorghum (Dogget and Eberhart, 1968) by utilizing male sterility system. Considering the success achieved in commercial exploitation of heterosis in cotton, sorghum, rice and such other often cross pollinated or self-pollinated crops, it is possible to visualize that such schemes of improving combining ability by following the recurrent selection schemes can be very well followed in these crops, with suitable modification in procedure in tune with the mating system of these crops (Patil and Patil, 2003).…”
Section: A Very New Methods To Develop Heterotic Groups Is Suggested Bmentioning
confidence: 99%